Pemahaman Makna Hadits Tinjauan Tekstual dan Kontekstual - IKLIL HASBIYALLA (SAMAWA, 2021)
The understanding of the text of the hadith always experiences dynamics, not unlike in the paradigm of the interpretation of the Qur'an. The terms of textual and contextual understanding that have been echoed by contemporary Muslim scholars are only a mapping, not a model of a solution, this problem is still a problem that needs to be reviewed and developed again. This study opens up horizons about the meaning of hadith both textually and contextually